Breakup and fragmentation behavior of molten material jet in multi-channel of BWR lower plenum. Issue 2 (1st February 2016) - Saito, Ryusuke; Abe, Yutaka; Yoshida, Hiroyuki
Abstract : To estimate the current status of reactor pressure vessel of Fukushima Daiichi nuclear power plant, it is important to clarify the breakup and the fragmentation behavior of molten material jet in boiling water reactor (BWR) lower plenum by a numerical simulation. To clarify the effects of complicated structures on jet breakup and fragmentation behavior, we conducted visualized experiments simulating the severe accident in the BWR by using the multi-channel experimental apparatus. In this study, the jet falling behavior, the jet breakup length, the fragmentation behavior and internal/external velocity profiles of the jet are observed by the backlight method and the particle image velocimetry. It is clarified that the complicated structures prolong the jet breakup length or make the fragments fall together to the lower plenum similar to the bulk state. In addition, it is clarified that strong shearing stress occurs at the crest of interfacial waves at the side of the jet. Finally, the fragment diameters measured in the present study well agree with the theory based on the shering stress by changing the coefficient term. Thus, it is suggested that the fragmentation mechanism is controlled by shearing stress and the fragment diameter can be estimated by adjusting the characteristic value.